Pengaruh Struktur Aset, Free Cash Flow dan Pertumbuhan Perusahaan Terhadap Kebijakan Hutang dengan Profitabilitas sebagai Variabel Intervening - Firyal Inko Veronisa; Harry Budiantoro; Perdana Wahyu Santosa; Kanaya Lapae (Forum Kerjasama Pendidikan Tinggi, 2023)
With profitability as an intermediary variable, this study seeks to understand how asset structure, free cash flow, and company growth affect debt policy. The population of this study were 26 food and beverage companies listed on the Indonesia Stock Exchange from 2017 to 2021, and 18 companies were used as research samples. Purposive sampling is the sampling method used. Multiple regression analysis was used to analyze the data, and then path analysis was added. The findings show that (1) asset structure has a negative effect on profitability. (2) Free cash flow has a positive effect on profitability. (3) The company's growth has no effect on profitability. (4) Asset structure has a negative effect on debt policy. (5) Free cash flow has a positive effect on debt policy. (6) The company's growth has a positive effect on debt policy. (7) Profitability has a negative effect on debt policy. (8) Profitability is able to mediate the effect of asset structure on debt policy. (9) Profitability is able to mediate the effect of free cash flow on debt policy. (10) Profitability is unable to mediate the effect of company growth on debt policy. The recommendations given in this study are that investors who are interested in investing should pay attention to the company's debt policy and the level of profitability so that later they can obtain a high rate of return; the company must be able to make good use of the asset structure that can be used as collateral for debt and be able to take advantage of Free Cash Flow and profitability to fund company operations, investment, and company expansion..